Principles of criminal law - Wallace, Harvey (Pearson/Allyn and Bacon, 2008)
This paperback text, briefer and significantly less expensive than its competitors, presents the basic concepts and principles of criminal law. The authors present the material in a straightforward and easy-to-read-and-understand format. They provide prevailing positions on specific issues, without going into lengthy explanations of majority and minority positions. This clarity of presentation allows them to include material not often found in other criminal law texts, such as white collar crime, victimless crime, political crime, and non- political crimes against the government. Companion materials, found at www.mycrimekit.com include a student study guide and casebook